Development of shape memory polyurethane based on polyethylene glycol and liquefied 4, 4′‐diphenylmethane diisocyanate using a bulk method for biomedical applications. Issue 4 (30th October 2014) - Mo, Funian; Zhou, Faxing; Chen, Shaojun; Yang, Haipeng; Ge, Zaochuan; Chen, Shiguo
<x xml:space="preserve">Abstract</x> Effects of hard segment content on structure, morphology and biocompatibility show that PEG‐based SMPUs bear both good shape memory effects and good biocompatibility when HSC is less than 35wt% <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>